(untitled) (New York, 1997)
This volume is a unique overview of cardiovascular development from the cellular to the organ level across a broad range of species. The first section focuses on the molecular, cellular, and integrative mechanisms that determine cardiovascular development. The second section has eight chapters that summarize cardiovascular development in invertebrate and vertebrate systems. The third section discusses the effects of disease and environmental and morphogenetic influences on nonmammalian and mammalian cardiovascular development. It includes strategies for the management of congenital cardiovascular malformations in utero and postnatally.
Keywords: Cardiovascular system,Cardiovascular system,Hệ tim mạch; Growth & development,Embryology,Phôi sinh học